Dynamics of the Use of Digital Media as a Source of Information During Media Transition - Ririt Yuniar; Diah Fitria Ningrum (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
There has been dynamic in the transition of the use of media by news readers from conventional media (Kompas print media) to new media (Kompas.com and KompasTV Instagram account). This causes a  change in the communication process starting from  the way of producing, delivering, capturing, and disseminating news as well as the content of the news itself which is different from people's habits earlier. The originality of this paper builds on the main ideas constructed from the theory of Uses and Gratification by focusing more on three aspects; audience, media (news content), and function of the media. This study uses a qualitative method with a constructivist analysis and a news content analysis unit that focuses on Kompas.com and KompasTV Instagram account at  the onset of Covid-19 pandemic  in March 2020 in Indonesia by mapping news content based on keywords for the Covid-19 pandemic and the Corona virus news search. This study found that the reading interest  among the Indonesian people is more inclined to news that has an audio-visual format than the newspaper format. This is evident from the audience’s  feedback in the comment section compiled from data findings. In addition, the lack of the audience’s  control results in  the poor communication culture among the people, so that there is a  potential for media bias and fake news. This study has limitations in  that it does not discuss the reader interest from the perspective of conventional news (Kompas print media). Therefore, there should be further comprehensive research by comparing the two types of media.